Fetal Skeletal Lethal Dysplasia: Case Report - Savoldi, Alexandre Mello; Villar, Maria Auxiliadora Monteiro; Machado, Heloisa Novaes; Llerena Júnior, Juan C. (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
The clinical management and decision-making in pregnancies in which there is suspicion of lethal fetal malformations during the prenatal period, such as lethal skeletal dysplasia (SD), demand a multidisciplinary approach coordinated by an experienced physician. Based on the presentation of a case of osteogenesis imperfecta type IIA, we offer and discuss recommendations with the intention of organizing clinical and laboratory investigations aiming toward the clinical management, prognosis, and etiological diagnosis of these malformations, as well as genetic counselling to patients who wish to become pregnant.
Keywords: pregnancy; skeletal dysplasia; osteogenesis imperfecta; prenatal period; genetic syndromes